The Influence of Product Quality and Price on Customer Satisfaction in UD Yuli Yadnya Wood Company in Kerobokan, Badung - I Putu Ditya Manguyoga; Nengah Ganawati (Fakultas Ekonomi Universitas Warmadewa, 2019)
In managing a business, the most important element in marketing a product is how the quality of the product itself and what prices will be sold to attract consumers. The products offered at UD Yuli Yadnya are teak wood, bengkirai wood and camphor. These products have different prices that match the quality of the product. The problem discussed in this research is the influence of Product Quality (X1) and price (X2) simultaneously and partially on customer satisfaction in UD. Yuli Yadnya wood company in Kerobokan, Badung. The samples used in this research were 30 respondents by distributing the Likert scale questionnaire with a simple random sampling method and accidental sampling technique. The instruments of this research were validity test and reliability test. The data analysis technique used is the classical assumption test that consists of a normality test with Kolmogorov-Smirnov analysis method, multicollinearity test and heteroscedasticity test with Glesjer analysis method that is then followed by multiple linear regression analysis. Hypothesis testing used the simultaneous significance test (f-test) and partial significance test (t-test). The results of the research of all independent variables are the f test showed that the independent variables consisting of product quality (X1) and price (X2) simultaneously have a positive and significant effect on consumer satisfaction in the wood company of UD Yuli Yadnya in Kerobokan, Badung. The t test shows that the product quality (X1) and price (X2) variables have a positive and significant influence on consumer satisfaction (Y) at UD Yuli Yadnya in Kerobokan, Badung.